Appearance Manifolds for Modeling Time-Variant Appearance of Materials - Wang, Jiaping; Tong, Xin; Lin, Steve; Pan, Minghao; Wang, Chao; Bao, Hujun; Guo, Baining; Shum, Harry (ACM Transactions on Graphics (TOG) - Proceedings of ACM SIGGRAPH 2006, 2006)
We present a visual simulation technique called appearance mani-folds for modeling the time-variant surface appearance of a material from data captured at a single instant in time. In modeling timevariant appearance, our method takes advantage of the key observation that concurrent variations in appearance over a surface represent different degrees of weathering. By reorganizing these various appearances in a manner that reveals their relative order with respect to weathering degree, our method infers spatial and temporal appearance properties of the material’s weathering process that can be used to convincingly generate its weathered appearance at different points in time. Results with natural non-linear reflectance variations are demonstrated in applications such as visual simulation of weathering on 3D models, increasing and decreasing the weathering of real objects, and material transfer with weathering effects.